2008
DOI: 10.2353/ajpath.2008.080129
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 Receptor Is Essential to Activate Microbicidal Mechanisms to Control Toxoplasma gondii Infection in the Central Nervous System

Abstract: Chemokines comprise a structurally related family of cytokines that regulate leukocyte trafficking. Because infection with Toxoplasma gondii can induce an important inflammatory reaction that, if left uncontrolled, can lead to death, we investigated the role of the chemokine receptor CCR2 in T. gondii infection. We orally infected CCR2 ؊/؊ mice with five ME-49 T. gondii cysts and monitored morbidity, survival, and immune response thereafter. The CCR2 ؊/؊ mice displayed higher susceptibility to infection as all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 40 publications
5
37
0
2
Order By: Relevance
“…We observed an increase in the expression of CCR1, CCR2, CCR4 and CXCR3 in the ileum and liver of infected mice (Figure 1A), as reported previously by our research group and others [12], [22], [23]. In addition, a concomitant down regulation of the Th2-related receptor CCR3 was observed in T. gondii infected mice, in accordance to the fact that eosinophils, mast cells or basophils are not the main leukocytes required for the control of this intracellular parasite.…”
Section: Resultssupporting
confidence: 89%
“…We observed an increase in the expression of CCR1, CCR2, CCR4 and CXCR3 in the ileum and liver of infected mice (Figure 1A), as reported previously by our research group and others [12], [22], [23]. In addition, a concomitant down regulation of the Th2-related receptor CCR3 was observed in T. gondii infected mice, in accordance to the fact that eosinophils, mast cells or basophils are not the main leukocytes required for the control of this intracellular parasite.…”
Section: Resultssupporting
confidence: 89%
“…Notably, CXCR2 KO mice, although reported to be healthy, also develop splenomegaly [29]. CCL2 (MCP-1) is a chemokine secreted by a variety of cells for the recruitment of monocytes, and in its absence, mice show increased susceptibility to a variety of infections including parasitic infections (eg, Toxoplasma gondii infection) [31]. In a recent study, AhR-KO mice were found to be more susceptible to T. gondii infection [32].…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Other CCRs, such as CCR1, CCR2 and CXCR2, have important roles in neutrophil proliferation and monocyte recruitment, which are essential for parasite control. [15][16][17][18] An early Th2 phenotype (driven by IL-4) is associated with bad outcome. 19,20 Antibodies and their Fc receptors (FcRs) have important roles as well.…”
Section: Immune Response In Acquired Toxoplasmosismentioning
confidence: 99%